Information technology and its use in the classroom - A Necessary boon or unwanted bane - Nadarajan, Shanthi (Centre for Academic Information Services, UNIMAS, 2014)
This article offers a critical overview of the cultural and educational benefits of the Information Technology era. It also looks into the dangers of the digital media especially for young people. It argues that the utopian concept of the multimedia age is more of a publicity hype and needs to be treated with caution. In contrast, there is a need for more measures and accounts of how young people perceive such technologies. It goes on to deal with previous research on children and pre-university students. The author calls for the need to pay importance to the transformation of learning, not only in theory but in the day to day practice of classrooms. Recent research into ICT and literary is reviewed, with suggestions for practical possibilites for cross – cultural collaborations and implications for the future are considered.